Effect of different salinity concentrations on hatching rate and larval development of Patin buah, Pangasius nasutus (Bleeker, 1863) - Jaapar, Muhamad Zudaidy; Muhammad Fitri, Yusof; Mohd Yusof, Hanan; Ramli, Nur Siti Fatimah; Mohamad, Siti Norita; Jamari, Zainoddin (Taylor & Francis, 2021)
The effects of water salinity on hatching rate and larval performance of Patin Buah (Pangasius nasutus) were studied. The fertilized eggs were incubated at 27.5–28°C in different concentrations of salinity (0, 1, 2, and 3 ppt) until hatch. The hatching rate of 0 ppt (48.6 ± 3.7%), 1 ppt (52.5 ± 3.7%), and 2 ppt (39.7 ± 6.4%) were significantly higher (P < 0.05) than in 3 ppt (14.8 ± 2.0%). The percentages of larval survival at day 30 were 65 ± 1.5%, 72 ± 5.0%, 57 ± 15.0%, and 32 ± 3.1% in 0 ppt, 1 ppt, 2 ppt, and 3 ppt respectively. Survival rates were significantly higher (P < 0.05) in 0 ppt and 1 ppt compared to 2 ppt and 3 ppt. This study reveals that salinity did not significantly improve hatching and the survival rate of P. nasutus, but 1 ppt could be used for the hatching process and larval nursing.